Association of C-type lectin-like receptor 2 and galectin-1 with portal vein system thrombosis in HBV-related liver cirrhosis - Zhang, Yiyan; Zhang, Xintong; Xu, Xiangbo; Guo, Xiaozhong; Xu, Shixue; Ma, Shaoze; Chen, Jihong; Qi, Xingshun (Frontiers in Medicine, 2023)
Background and aims: Hepatitis B virus (HBV) infection is the most common cause of liver cirrhosis in China. Portal venous system thrombosis (PVST) is a major complication of liver cirrhosis. Recently, it has been shown that C-type lectin-like receptor 2 (CLEC-2) and galectin-1 participate in the activation and aggregation of platelets, thereby promoting the development of thrombosis. This cross-sectional study aims to evaluate the association of serum CLEC-2 and galectin-1 levels with PVST in patients with HBV-related liver cirrhosis. Methods: Overall, 65 patients with HBV-related liver cirrhosis were included, of whom 23 had PVST and 42 did not have. Serum CLEC-2 and galectin-1 levels were measured using enzyme-linked immunosorbent assay kits. PVST was assessed by contrast-enhanced computed tomography and/or magnetic resonance imaging scans. Subgroup analyses were conducted according to the degree and location of PVST. Results: Patients with PVST had significantly higher serum CLEC-2 (P=0.006) and galectin-1 (P=0.009) levels than those without. Patients with partial/complete PVST or fibrotic cord (P=0.007; P=0.002), but not those with mural PVST (P=0.199; P=0.797), had significantly higher serum CLEC-2 and galectin-1 levels than those without PVST. Patients with superior mesenteric vein thrombosis had significantly higher serum CLEC-2 (P=0.013) and galectin-1 (P=0.025) levels than those without PVST. Patients with main portal vein thrombosis had higher serum CLEC-2 (P=0.020) and galectin-1 (P=0.066) levels than those without PVST, but the difference in serum galectin-1 level was not significant between them. Conclusion: Serum CLEC-2 and galectin-1 levels may be associated with the presence of PVST in HBV-related cirrhotic patients, but this association should be dependent upon the degree of PVST.